Comparison of manual therapy techniques on ankle dorsiflexion range of motion and dynamic single leg balance in collegiate athletes. (January 2022) - Lehr, Michael E.; Fink, Michael L.; Ulrich, Erin; Butler, Robert J.
Abstract: Introduction/purpose: Literature consistently identifies two key examination components when managing ankle/foot pathologies: 1) dorsiflexion range of motion (DFROM) and 2) single limb balance. Mobilizations with movement (MWM) and Instrument-Assisted Soft Tissue (IASTM) are two emerging manual therapy (MT) options in the management of ankle/foot conditions. Methodology/sample: In this observational cohort study, 147 subjects were randomized in a block fashion as follows: 1) Control, 2) IASTM, 3) MWM, and 4) Combination of both MT interventions. Descriptive statistics of the sample were conducted with integrity checks followed by comparative analysis for mean change between the variables or DFROM and YBTLQ ™ performance. Results: ANOVA Welch's F indicated significant differences between the treatment conditions (Welch's F (3, 75.669) = 4.533, p = .006). Games-Howell post hoc tests indicated significantly more change in DFROM in the IASTM (p = .043) and CKCMOB (p = .026) conditions when they were administered as single treatments, than in the Control Condition or when the treatments were combined. Dynamic balance, as measured by the YBT-LQ™, did not yield a significant response based on the intervention arm. Discussion/clinical relevance: Specifically, IASTM or closed kinetic chain (CKC) MWM MT techniques used in isolation can be considered a cost-effective intervention that can be administered by a skilled MT practitioner in a "low risk-high reward" clinical scenario with potential biomechanical and neurophysiological benefits for improving CKCDFROM. Highlights: CKCDFROM and YBT-LQ are two reliable and valid tests that can be administered during ankle/foot management. CKCMWM and IASTM are two-cost-effective, non-invasive MT viable options aimed at improving CKCDFROM. Compounding MT techniques such as CKCDFROM and IASTM at the ankle region in one session may minimize benefits of improving CKCDFROM.